Great saphenous vein stripping using nasogastric tub (2012)
Background; Crossectomy and Great Saphenous Vein (GSV) stripping remains the gold standard of treatment for great saphenous varicose vein. Many techniques of GSV stripping have been described. However, very few hospitals in developing countries are equipped with a vein stripper. Method and result: We describe the use of nasogastric tube in the stripping of GSV. This simple technique has been successfully applied in three patients. Conclusion: There is a need to carry out a prospective study regarding the application of this technique of GSV stripping.